SKRINING FITOKIMIA EKSTRAK ETANOL 80% ROSEMARY (Rosmarinus officinalis L.) DENGAN METODE EKSTRAKSI DIGESTI - Evi Priyatno; Mercyska Suryandari (Akademi Farmasi Yarsi Pontianak, 2022)
Rosemary (Rosmarinus officinalis L.) in the Lamiacea family is one of the herbal plants that has medicinal properties. Based on its potential benefits, a phytochemical screening study was conducted to determine the class of secondary metabolites contained in it and to test the ability of 80% ethanol for extracting secondary metabolites from rosemary extract using the digestion extraction method. The filtrate was then concentrated using a rotary evaporator and phytochemical screening tests were carried out by observing the presence of color changes, formation of precipitates, and the formation of stable foam using certain reagents. The results showed that the ethanol extract of 80% rosemary was positive for terpenoids, alkaloids, flavonoids, saponins, tannins, and polyphenols